OPRA: Gerakan Perempuan Adat pada Suku Bangsa Namblong di Lembah Grime di Kabupaten Jayapura - Elisabet Asrida Sulastri; Marlina Flassy; Akhmad Akhmad (CENDERAWASIH: Jurnal Antropologi Papua, 2020)
This article aims to describe and analyze the social movements carried out by the OPRA (“Organisasi Perempuan Adat” or Indigenous Women's Organization) in the Namblong Tribe in the Grime Valley, Jayapura Regency, Papua. This research is a qualitative research with an ethnographic approach. Determination of selected informants by snowball involving key informants from OPRA. The data collection techniques used were in-depth interviews and observations, as well as FGD (Focus Group Discussion). Data analysis includes the stages of data reduction, data exposure and data interpretation. The results showed that the OPRA organization in the Namblong ethnic group was born because it was initiated by a group of women who were dissatisfied with the placement of women in the customary structure. The increasing number of women from the Namblong tribe who became victims of violence and unfair treatment, raised a collective awareness among them to rise up against and fight for their rights and demand justice and equality for Namblong women. The formation of the ORPA shows how customary identities are used and institutionalized not only as an effort to maintain power against the State and companies in matters of rights to land, natural resources and culture but also to fight for women's rights in the Namblong community